2011
DOI: 10.1103/physreve.84.031407
|View full text |Cite
|
Sign up to set email alerts
|

Systematic modification of the rheological properties of colloidal suspensions with polyelectrolyte multilayers

Abstract: Tailoring rheological properties of colloidal suspensions with the adsorption of polyelectrolyte multilayers (PEMs) is based on the idea of controlling macroscopic mechanical properties by modifying the particle surface in a reproducible and well-understood manner. With layer-by-layer self-assembly, monodisperse polystyrene particles are coated with up to ten layers of the oppositely charged strong polyelectrolytes: poly(diallyl dimethyl ammonium chloride) and poly(styrene sulfonate). The conformation of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is also found that a master curve at low frequency can be constructed from moduli under different oscillatory shear rates, where the shifting factor for frequency exhibits evident dependency on the strain rate amplitude. Such behaviors are also observed in other complex fluids such as suspensions, colloids, foams, and block copolymers (175), (217,218). Note that the SRFS mater curve could not represent the linear response especially at low frequency due to its nonlinear characteristics (216).…”
Section: Series Shearmentioning
confidence: 74%
“…It is also found that a master curve at low frequency can be constructed from moduli under different oscillatory shear rates, where the shifting factor for frequency exhibits evident dependency on the strain rate amplitude. Such behaviors are also observed in other complex fluids such as suspensions, colloids, foams, and block copolymers (175), (217,218). Note that the SRFS mater curve could not represent the linear response especially at low frequency due to its nonlinear characteristics (216).…”
Section: Series Shearmentioning
confidence: 74%
“…A colloidal system can be either dispersed or flocculated depending on the charge fluctuations in the solvent medium and the particle volume fraction. 29,30 The variation of storage modulus, G 0 and loss modulus, G 00 as a function of increasing strain amplitude from 0.1% to 100% are shown in Fig. 10.…”
Section: Conformation Changes In Pecmentioning
confidence: 99%
“…Additionally, SRFS was found to significantly overestimate the rate of terminal relaxation for kinetically arrested suspensions. Thus, the relevance of the information uncovered by these methods to the understanding of quiescent glasses is debatable. , Alternatively, a time–concentration or time–composition superposition (TCS) principle has long been used in conjunction with small-amplitude oscillatory shear (SAOS) measurements to extend the rheological map for entangled polymers, triblock copolymers, microgels, and particle suspensions, ,, by overlying G ′ and G ″ data measured at multiple concentrations, with respect to a reference fluid state that may be chosen at any concentration. In a previous publication we demonstrated that suspensions with particle concentrations that bracket the liquid-to-glass transition obey an analogous TCS superposition principle that allows a complete master curve for their relaxation dynamics to be constructed, providing access to in-cage glassy dynamics as well as dynamics at the uncaging transition …”
mentioning
confidence: 99%